PENGUMPULAN DATA CERITA RAKYAT BONTANG SEBAGAI BAHAN LITERASI BERBASIS KEARIFAN LOKAL - Ariani, Setya; Valiantien, Nita Maya; Alamsyah; D, Dahri; Nasir, Muhammad Alim Akbar; Irni (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2023)
Folklore, serving as a cultural manifestation within Indonesian society, encompasses esteemed principles of local wisdom whose existence needs to be maintained and preserved. While maintaining the essence of the original narrative, folklore that develops in the community generally has multiple versions. The presence of multiple speakers contributes to the narrative's delivery. A team of lecturers and student from the Faculty of Cultural Sciences conducted Community Service (PKM) activity to collect folklore data. This was accomplished through conducting interviews with two individuals who are members of community institutions in the Bontang Kuala area. Numerous titles of folklore compiled based on the narrative of the speakers are Beras Basah, Tanjung Mamat/Hantu Tausan, Nek Gembong, Lok-Lope, Mak Bondan, Ikan Barakuda, Datuk Seman dan Kangkung, as well as Sungai Belanda. The values of local wisdom that can be learnt from these narratives are the consistent practice of generosity, the cultivation of honesty in both speech and conduct, the conscientious pursuit of a healthy lifestyle, and the preservation of the natural environment.